(untitled) (Research, Society and Development, 2021)
To evaluate the shear bond strength and the fracture type of orthodontic tubes bonded directly with composite resin throughout the enamel surface. 30 bovine teeth were cut into 3 slices with 5 mm each and embedded in PVC pipes with acrylic resin exposing the buccal face. Subsequently, the teeth were submitted to conventional bonding techniques. Natural Ortho resin was applied for direct bonding of Edgewise Standard orthodontic tubes (Morelli®) and light-cured for 20s. A different viscosity resin was chosen and light-cured for 40s to reinforce the tube surface. The samples were divided into the following groups: Orthodontic tube with direct bonding without reinforcement (CONTROL), Tube with Natural Ortho resin + Reinforcement (NO + NO), Tube with Natural Ortho resin + Reinforcement with Flow resin (NO + FL). These were submitted to shear bond strength; immediate and 1-year aging fracture analysis after simulated through thermocycling. In the shear bond strength test, the group of orthodontic tubes that were directly bonded with Natural Ortho resin and reinforced (NO + NO) showed greater strength results after 24 hours and 1 year with values of (p=0.0225) and (p=0.0273). It was statistically differentto the NO + FL and CONTROL reinforced groups. In the fracture analysis, the NO +NO group was classified immediately as composite cohesive, and mixed failure after aging by thermocycling. The addition of a composite resin layer on the surface of the directly bonded orthodontic tube improved bond strength. The reinforcement must be carried out in regular consistency and the use of Flow resin is not indicated.